2020
DOI: 10.1016/j.afjem.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Haddon matrix conceptual model to guide motor vehicle crash injury research and prevention in Botswana

Abstract: Introduction Little literature addresses the burden of injury in Botswana, including trauma from motor-vehicle crashes (MVCs). In response, the University of Botswana and the Botswana Ministry of Health and Wellness are collaborating with the University of Pennsylvania to enhance injury and trauma research capacity in Botswana. Here we describe this training program and a research exercise to identify opportunities to prevent, through future research and countermeasures, MVCs specifically in Botsw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…16,17 Studies outside India have also reported traffic rule violations to be the major cause of road accidents, along with environmental factors like poor street lighting and lack of road signs. [18][19][20][21] These studies emphasize the importance of enforcing traffic regulations, and conducting behavior change education regarding traffic safety rules and their adherence.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Studies outside India have also reported traffic rule violations to be the major cause of road accidents, along with environmental factors like poor street lighting and lack of road signs. [18][19][20][21] These studies emphasize the importance of enforcing traffic regulations, and conducting behavior change education regarding traffic safety rules and their adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection instrument used in this study was derived from the Haddon Matrix, a highly acknowledged and influential framework in injury prevention. The matrix, developed by William Haddon in 1970, 15 analyses a range of factors related to individual characteristics, features of the vector or agent, and environmental variables before, during, and after an injury or fatality. Hence, the risk assessment form successfully identifies three distinct elements.…”
Section: The Instruments and Data Collectionmentioning
confidence: 99%
“…Intrinsic risk factors were inherent, personal factors attributed to driver characteristics and riding behaviors. They formed the agentbased risk factors according to the Haddon matrix [33,34]. The intrinsic factors (gender, age) were differentiated from the modifiable risk factors (e.g., helmet use).…”
Section: Synthesis and Haddon Matrixmentioning
confidence: 99%